Photovoice, emergency management and climate change: a comparative case-study approach. (August 2021) - Russo, Samantha; Hissa, Kylie; Murphy, Brenda; Gunson, Bryce
Photovoice aims to enable people to record and reflect their community's strengths and challenges, to encourage group dialogue and knowledge about important issues through group discussions and to inform policymaking. While primarily utilized in the health field, an emerging area of focus is to use photovoice in an emergency management or climate change context. Through work conducted in two rural areas recovering from natural disasters in Ontario, Canada, this research, focused on critical infrastructure disaster recovery, underscores the value of undertaking a comparative case-study approach and offers a detailed reporting of the fieldwork methodology. We argue that photovoice has the potential to solicit poorly understood rural and Indigenous community member perspectives, thereby augmenting locally relevant, place-based information and, ideally, empowering voices that are often under-represented in municipal and provincial decision-making processes. We offer lessons learned related to the project's processes and outcomes, and outline the applicability of photovoice for emergency management and climate change research.